The influence of early neutrophil-Leishmania interactions on the host immune response to infection - Ribeiro-Gomes, Flavia; Sacks, David (Frontiers in Cellular and Infection Microbiology, 2012)
Neutrophils are the first cells recruited to the dermal site of Leishmania infection following injection by needle or sand fly bite. The role of neutrophils in either promoting or suppressing host immunity remains controversial. We discuss the events driving neutrophil recruitment, their interaction with the parasite and apoptotic fate, and the nature of their encounters with other innate cells. We suggest that the influence of the neutrophil response on infection outcome critically depends on the timing of their recruitment and the tissue environment in which it occurs.